Elevated serum uric acid is associated with peripheral endothelial dysfunction in women. (November 2019) - Taher, Riad; Sara, Jaskanwal D.; Prasad, Megha; Kolluri, Nikhil; Toya, Takumi; Lerman, Lilach O.; Lerman, Amir
Abstract: Background and aims: Both elevated serum uric acid (SUA) and peripheral endothelial dysfunction (PED) are associated independently with cardiovascular disease (CVD). However, the association between SUA and PED is yet to be established. We hypothesized that high normal range of SUA is associated with PED. Methods: We performed a retrospective cross-sectional analysis of patients who were referred to Mayo Clinic between 2006 and 2014 for routine cardiovascular evaluation and who underwent evaluation of Reactive Hyperemia Peripheral Arterial Tonometry (index <2 consistent with PED). A high UA was defined as ≥5 mg/dL, in keeping with previous studies evaluating the link between SUA and CVD outcomes. Results: One hundred forty patients were included (mean age 50.7 ± 12.9 years, 86 (61.4%) female). Twenty four patients (17.1%) had pre-existing CVD (8 (9.3%) in females). Thirty patients (21.6%) had a Framingham score > 10% (8 (9.4%) in females). Fifty eight (41.4%) had PED and 77 (55.0%) had an elevated SUA. SUA levels were higher in patients with PED compared to those without (5.5 ± 1.4 vs 4.8 ± 1.2 mg/dL; p = 0.004). In an univariate analysis, elevated SUA levels were associated with PED (Odds Ratio (OR): 2.7; 95% confidence interval [CI] 1.33–5.48; p = 0.005). In a multivariate analysis adjusting for age, sex, presence of obstructive CVD and Framingham score>10, elevated SUA levels were associated with PED (OR 2.45; 95% CI 1.08–5.52; p = 0.031). After stratifying by sex, this association persisted in females only. Conclusions: High normal SUA levels are associated with PED in women who are otherwise at low risk for CVD. Thus, SUA is a promising circulating biomarker that could be used to assist in risk stratification in female patients with chest pain and/or those undergoing evaluation of CVD risk. Highlights: Serum uric acid is associated with microvascular peripheral endothelial dysfunction. Uric acid threshold for vascular health is lower than the upper normal range limit. Uric acid is associated with vascular health in apparently low risk individuals.